Study of comparative proteome between normal and inverted karyotypes of human mesenchymal stem cells - de Souza Santos, John Lenon; Câmara, Alice Barros; Meira, Isabella Tanus Job e; Oliveira, Jonas Ivan Nobre (Acta Scientiarum. Biological Sciences, 2020)
Multipotent mesenchymal stem cells have been expanded in vitro for cellular therapy in numerous clinical settings without standardized culture conditions or quality-control schemes. The in vitro expansion is necessary to obtain sufficient cells for clinical applications. However, the expansion may induce genetic and functional abnormalities which may affect the safety and functionality of MSC, especially the chromosomal stability. This study aimed to investigate the protein profile of umbilical cord-derived MSC with normal and inverted karyotypes after expansion in the laboratory. Mass spectrometry analysis was performed and the Bradford method, Scaffold software, String and Cytoscape databases were employed to measure and characterize the protein content of umbilical cord-derived MSC. Networks of protein interactions, hub and bottleneck proteins were identified by proteomics and systems biology approaches. We found that proteins related to cellular stress were super expressed in inverted karyotype cells. Moreover, a high expression of Serpine 1, RHOA, and CTSB was found in these cells, which are proteins related to cancer. The albumin and ubiquitin proteins have been associated with a positive prognosis in cancer and cellular stress, and were up- and down-regulated in normal karyotype cells, respectively. The results suggests that the paracentric inversion inv(3)(p25p13) induced some type of cellular stress and genetic instability in human mesenchymal stem cells. These analyses showed the importance of carrying out studies related to the genetic instability of human mesenchymal stem cells using the protein expression profile as a parameter.